Dithiocarbamate as a Valuable Scaffold for the Inhibition of Metallo-β-Lactmases - Ying Ge; Li-Wei Xu; Ya Liu; Le-Yun Sun; Han Gao; Jia-Qi Li; Kewu Yang (Biomolecules, 2019)
The ‘superbug’ infection caused by metallo-β-lactamases (MβLs) has grown into an emergent health threat. Given the clinical importance of MβLs, a novel scaffold, dithiocarbamate, was constructed. The obtained molecules, DC1, DC8 and DC10, inhibited MβLs NDM-1, VIM-2, IMP-1, ImiS and L1 from all three subclasses, exhibiting an IC50 < 26 μM. DC1 was found to be the best inhibitor of ImiS (IC50 < 0.22 μM). DC1-2, DC4, DC8 and DC10 restored antimicrobial effects of cefazolin and imipenem against E. coli-BL21, producing NDM-1, ImiS or L1, and DC1 showed the best inhibition of E. coli cells, expressing the three MβLs, resulting in a 2-16-fold reduction in the minimum inhibitory concentrations (MICs) of both antibiotics. Kinetics and isothermal titration calorimetry (ITC) assays showed that DC1 exhibited a reversible, and partially mixed inhibition, of NDM-1, ImiS and L1, with Ki values of 0.29, 0.14 and 5.06 µM, respectively. Docking studies suggest that the hydroxyl and carbonyl groups of DC1 form coordinate bonds with the Zn (II) ions, in the active center of NDM-1, ImiS and L1, thereby inhibiting the activity of the enzymes. Cytotoxicity assays showed that DC1, DC3, DC7 and DC9 have low toxicity in L929 mouse fibroblastic cells, at a dose of up to 250 μM. These studies revealed that the dithiocarbamate is a valuable scaffold for the development of MβLs inhibitors.